Ethnic stereotypes in the speech behavior of a modern linguistic personality - Marina Ch, Shogenova; Zalina R., Dokhova (Kavkazologiya, 2024)
The work was carried out within the framework of the study of the actual problem of determining language, culture, and man, which takes on a special status in the context of understanding the im-portance of language in its relation to ethnic culture as a set of people's unique non-transitory val-ues and life orientations. The study's primary assumption is that a certain people's ethnic image is kept in their lan-guage, and its dominating qualities are transferred into the speech behavior of a linguistic person-ality.The purpose of the article is to consider ethnic stereotypes as constants of cognitive con-sciousness, a means of representing the specifics of speech behavior of a modern linguistic per-sonality in typical communicative situations. The research material was the texts created in the language of the Adyghe personality, which used stereotypical lexical units as figurative stable expressions, actively used in ethnic culture and understood as a concentration of priority knowledge and meanings subordinated to a single value-behavioral system adopted in the cultural and linguistic space of the Adyghe ethnic group. The examination of linguistic units offers grounds to recognize that the incorporation of ste-reotyped phrases in current speech interaction contributes not only to the translation of communi-catively relevant ethnic information, and also establishes the conceptual paradigm of dominant meanings, knowledge and perceptions, forming the cognitive consciousness of the modern eth-nocultural linguistic personality and regulate its speech behavior in different communicative situ-ations.